Enzymatic And Non-Enzymatic Anti-Oxidant Status Of Breast Cancer Patients In Tamilnadu - S. SIVAKUMAR; S. NIRANJALI DEVARAJ (International Journal of Pharma and Bio Sciences, 2011)
Breast cancer is a global public health problem as it is the third most common cancer leading to the death of women worldwide. The aim of the study was to find out anti-oxidant status of breast cancer patients in Tamilnadu. This study has been conducted on breast cancer patients admitted to Government Cancer Hospital, Kanchipuram, Tamilnadu. Fifty breast cancer patients and normal persons of an equal number of age and sex matched disease-free healthy subjects were used for data analysis. The levels of antioxidants’ status in breast cancer patients and healthy subjects were assayed using colorimetric methods. Enzymatic antioxidants like Superoxide Dismutase, Catalase, Glutathione Peroxidase, Glutathione Transferase and Non-enzymatic antioxidants like Vitamin C and E were decreased significantly. Reduced Glutathione levels also decreased. The low availability of peroxidizable substrates and antioxidant capacity concluded that the oxidative stress induced in breast cancer patients confer a selective growth of breast cancer cells.